Infectivity and Progression of COVID-19 Based on Selected Host Candidate Gene Variants - Iyer, Gayatri R.; Samajder, Sayani; Zubeda, Syeda; S, Devi Soorya Narayana; Mali, Vishakha; PV, Sharath Krishnan; Sharma, Anuradha; Abbas, Neyha Zainab; Bora, Nandini Shyamali; Narravula, Amulya; Hasan, Qurratulain (Frontiers in Genetics, 2020)
Introduction: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has spread around the globe. Susceptibility has been associated with age, biological sex, and other prior existing health conditions. However, host genes are involved in viral infectivity and pathogenicity, and polymorphisms in these could be responsible for the interethnic/interindividual variability observed in infection and progression of COVID-19. Materials and Methods: Clinical exome data of 103 individuals was analyzed to identify sequence variants in five selected candidate genes: ACE2, TMPRSS2, CD209, IFITM3, and MUC5B to assess their prevalence and role to understand the COVID-19 infectivity and progression in our population. Results: A total of 497 polymorphisms were identified in the five selected genes in the exomes analyzed. Thirty-eight polymorphisms identified in our cohort have been reported earlier in literature and have functional significance or association with health conditions. These variants were classified into three groups: protective, susceptible, and responsible for comorbidities. Discussion and Conclusion: The two polymorphisms described in literature as risk inducing are rs35705950 in MUC5B gene and TMPRSS2 haplotype (rs463727, rs34624090, rs55964536, rs734056, rs4290734, rs34783969, rs11702475, rs35899679, and rs35041537) were absent in our cohort explaining the slower infectivity of the disease in this part of India. The 38 functional variants identified can be used as a predisposition panel for the COVID-19 infectivity and progression and stratify individuals as “high or low risk,” which would help in planning appropriate surveillance and management protocols. A larger study from different regions of India is warranted to validate these results.